Q&A: The status of ICTs in integrated pest management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
In a recent interview, Dr. Yunlong Xia, Head of the Information Technology and Bioinformatics Department at the International Centre of Insect Physiology and Ecology (ICIPE) in Kenya, provided an overview of the status of and trends in the use of I